Increasing Teacher Professionalism through Principal Instructional Leadership (Study at Private Vocational School 2 Taman Siswa Pematang Siantar) - Susilawaty, Susilawaty; Mhd. Isman; Salim Aktar (JURNAL PENDIDIKAN IPS, 2024)
The purpose of this study is to examine how the principle of SMK 2 Taman Siswa Pematang Siantar has increased teacher professionalism through instructional leadership. This kind of research employs a qualitative methodology that includes the case study technique, observation, interviews, and documentation studies as methods of data collecting. The research's findings indicate that, when given the right guidelines and procedures, school principals can adopt leadership practices that enhance teachers' professionalism. This is evident in three ways: first, teachers participate in different training programs, workshops, and seminars to enhance their pedagogical skills. The second step involves carrying out teacher professional development via supervision (visits to classes) and performance evaluation (keeping an eye on how learning activities are being developed). In an effort to enhance the school, the principal fosters a cooperative, transparent, and amicable environment with the instructors. The implication of this research is that instructional leadership is important for school principals to practice because it contains elements of direction, involvement, development, supervision and improving the quality of teacher performance as professional educators.